1979
DOI: 10.1111/j.1471-0528.1979.tb11254.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fetal Head Compression and Fetal Acidaemia During Labour on Human Fetal Cerebral Function as Measured by the Fetal Electroencephalogram

Abstract: We investigated the effect of head compression and acidaemia during labour in 25 African primigravidae. Evidence that head compression had occurred during labour was confirmed by both clinical and radiological means at the end of a trial of labour. No significant difference could be demonstrated in the quantity of fetal electroencephalogram (EEG) abnormality that occurred in the groups with marked head compression as compared to the groups without marked head compression. Deterioration in the fetal EEG to a fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 13 publications
2
13
0
Order By: Relevance
“…These effects may be due to the effects of hypoxia and acidosis in labour, excessive head compression or intrauterine infection, or any combination of these causes. Recent evidence, however, suggests that compression of the fetal head in labour is safe provided that fetal acidosis does not occur (Wilson et al 1979). Thus, it is safe to conduct a trial of labour until fetal distress occurs, whereupon the trial must be terminated immediately.…”
Section: Discussionmentioning
confidence: 99%
“…These effects may be due to the effects of hypoxia and acidosis in labour, excessive head compression or intrauterine infection, or any combination of these causes. Recent evidence, however, suggests that compression of the fetal head in labour is safe provided that fetal acidosis does not occur (Wilson et al 1979). Thus, it is safe to conduct a trial of labour until fetal distress occurs, whereupon the trial must be terminated immediately.…”
Section: Discussionmentioning
confidence: 99%
“…The interesting study by Wilson et al argues quite strongly against an adverse effect of fetal head compression 17. In a small study of 25 human high-risk labors with frequent administration of oxytocin, they demonstrated that the fetal EEG was not related to fetal head pressure as assessed by severe head molding but was related to systemic acidosis.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of head compression associated with cephalopelvic disproportion on fetal brain activity was studied and no significant differences in fEEG findings between the group with cephalopelvic disproportion and the group without it were noted (21).…”
Section: Long-term Outcomementioning
confidence: 99%
“…The information gathered from fEEG, FHR monitoring, scalp pH measurements, Apgar score used as control measures of fetal health, and their relationships with one another were studied and the invaluable information they can provide have been demonstrated in several studies (15,21,23,25,26,31). The 2019 Early Notification scheme progress report of the National Health System identified 70% of perinatal brain injuries as avoidable with continuous CTG monitoring (84).…”
Section: Summary Of Evidencementioning
confidence: 99%
See 1 more Smart Citation